Sleep in Antarctica: from the Sleep Disturbances Towards All the Challenges - Shylo , Oleksandr; Lutsenko , Dmytro; Lutsenko , Olena; Babiychuk , Georgiy; Moiseyenko, Yevgen (Problems of Cryobiology and Cryomedicine, 2020)
From the first expeditions, adaptation to the harsh environment of Antarctica, the expeditionists complained of a trouble sleeping. During a long stay on the continent, the polar explorers are exposed to a large number of extreme environmental factors both at the station and outside it, but the main physical factors of sleep disturbances are considered to be the peculiarities of light and photoperiod. Recently, more attention has been paid to clarifying the role of psychological adaptation to the Antarctica conditions, regarding the living in a small group and confined space. Existing methods to prevent the sleep disorders, first of all, comprise the manipulating with light parameters, activity and rest schedules. A thorough preliminary selection of expeditionists to establish the necessary psychological climate, thinking about gender and multicultural characteristics of adaptation can also be considered with the perspective of preventive measures. At the same time, little attention is paid to the investigation of the role of 'non-core' factors (chronotype, personality traits and features of personal adaptation to the extreme environment of Antarctica), as well as forced contact with cold, affecting sleep. Probl Cryobiol Cryomed 2020; 30(1): 3-23 С первых экспедиций адаптация их участников к суровым условиям Антарктиды сопровождалась жалобами на нарушения сна. В ходе длительного пребывания на континенте полярники подвергаются воздействию большого количества экстремальных факторов окружающей среды как на станции, так и вне ее пределов, но основными физическими причинами, вызывающими нарушения сна, принято считать особенности освещенности и фотопериода. В последнее время более пристальное внимание уделяется выяснению роли психологической адаптации к условиям Антарктиды с учетом жизни в малой группе и замкнутом пространстве. Существующие методы противодействия нарушениям сна, в первую очередь, включают манипулирование параметрами освещенности, графиком работы и отдыха. Тщательный предварительный отбор участников для создания необходимого психологического климата, учет гендерных и мультикультурных особенностей адаптации также можно рассматривать с позиции превентивных мер. При этом изучению роли «неосновных» факторов (хронотип, личностные черты и особенности персональной адаптации к экстремальным условиям Антарктиды), а также вынужденного контакта с холодом, влияющих на сон, уделяется незначительное внимание. Probl Cryobiol Cryomed 2020; 30(1): 003–023 З перших експедицій адаптація їх учасників до суворих умов Антарктиди сопроводжувалась скаргами на порушення сну. Протягом тривалого перебування на континенті полярники піддаються впливу великої кількості екстремальних факторів оточуючого середовища як в умовах станції, так і за її межами, але основними фізичними чинниками, які призводять до порушення сну, прийнято вважати особливості освітленості і фотоперіоду. Останнім часом більш прискіплива увага приділяється виясненню ролі психологічної адаптації до умов Антарктиди з урахуванням перебування в умовах малої групи і замкненого середовища. Існуючі методи протидії порушенням сну, в першу чергу включають маніпулювання параметрами освітленості, графіком роботи та відпочинку. Ретельний попередній відбір учасників для створення необхідного психологічного клімату, враховування гендерних і мультикультурних особливостей адаптації також можна розглядати з позиції превентивних мір. При цьому вивченню ролі «неосновних» факторів (хронотип, особистісні риси і особливості персональної адаптації до екстремальних умов Антарктиди), а також вимушеного контакту з холодом, які впливають на сон, не приділяється значної уваги. Probl Cryobiol Cryomed 2020; 30(1): 003–023